Antibiotics Without Prescription: Factors Affecting Sales and Purchases in the South Banjarbaru District - Rahmayanti Fitriah; Ramilah Audini Miftahul Jannah; Rahmi Hidayati (Universitas Lambung Mangkurat, 2026)
Antibiotics are drugs used to treat bacterial infections and should only be obtained with a doctorâ€™s prescription. However, many people in Indonesia acquire them without one, and regulations are not fully enforced across regions. This study aimed to identify factors influencing the sale and purchase of non-prescription antibiotics. A quantitative approach was used, employing purposive sampling for sales factors and proportional random sampling for purchase factors, with data collected via questionnaires. Data were analyzed using univariate (frequency distribution), bivariate (Kendallâ€™s tau test), and factor analysis methods. Results showed that antibiotic sales without prescriptions were at a moderate level (50%), while purchases were at a low level (65.3%). There was no significant relationship between antibiotic sales and purchases without prescriptions in South Banjarbaru District. The factors that most influence sales are integrity, financial, legal and critical sense, as well as external pressure, while the factors that influence purchasing are integrity, financial,Â ease of access, knowledge, and recommendations/information from others.